Effectiveness of Natalizumab in Achieving No Evidence of Disease Activity (NEDA-3)—Data From a Local Norwegian Cohort - Jaklin, Andreas K.; Benjaminsen, Espen; Alstadhaug, Karl Bjørnar (Frontiers in Neurology, 2021)
Objective: We aimed to determine the effectiveness of natalizumab (NTZ) by assessing overall No Evidence of Disease Activity 3 (NEDA-3) in a local Norwegian cohort. Background: NTZ is an immunomodulating drug used in the treatment of multiple sclerosis (MS). It has typically been used as a second-line treatment, but certain patients with high disease activity have started directly with NTZ. Methods: This retrospective cohort study includes all patients who received NTZ for relapsing–remitting MS at Nordland Hospital in the period 2008–2018. In June 2019, status for every patient was assessed, and a survival curve was used to show the cumulative probability of achieving NEDA-3 over time. Results: The cohort consisted of 66 patients, 49 women and 17 men with a mean age of 40.0 ± 10.8 years. Each patient received on average 45.8 ± 36.4 NTZ infusions. Mean age and Expanded Disability Status Scale (EDSS) at first infusion was 34.8 ± 10.5 and 3.2 ± 1.9, respectively. Prior to NTZ treatment, 83% had used other disease modulating drugs and 65% were anti-JC virus (JCV) seronegative. During the study period, seven patients converted to seropositive. In 2019, 40 patients had switched or stopped treatment: 19 due to positive JCV serostatus, 9 due to disease activity, 7 due to adverse effects or complications (1 progressive multifocal leukoencephalopathy), 2 due to pregnancy, and 3 due to autologous hematopoietic cell transplantation abroad. Three patients experienced rebound in the wake of discontinuation (7.5%). Of the patients receiving NTZ for more than 3 years (n = 33), 50% had achieved NEDA-3 after 3 years. Compared to those with evidence of disease activity (EDA), these NEDA-3 patients had significant lower EDSS score before first NTZ treatment (p = 0.04). They were also slightly, but not significantly, younger at debut of their MS, at the diagnosis and at first NTZ treatment. Of all the patients who ever started on NTZ, 23% had achieved NEDA-3 5 years later. The mean EDSS in 2019 was 3.6 ± 2.5. Conclusion: Despite ...